Answers

2015-05-01T01:44:51+05:30
x + 2y = 0.8
10x + 5y = - 7

x + 2y = 0.8
x = 0.8 - 2y

10x + 5y = - 7 (x = 0.8 - 2y)
10*(0.8 - 2y) + 5y = - 7
8 - 20y + 5y = - 7
8 - 15y = - 7
- 15y = - 7 - 8
- 15y = - 15
- y = - 15/15
-y = -1 * (-1)
y = 1

x = 0.8 - 2y (y = 1)
x = 0.8 - 2*(1)
x = 0.8 - 2
x = - 1.2
-----------------------------------------------------------------------------------------------------
x + 2y = 0.8
10x + 5y = - 7

x = -1.2 , y = 1

- 1.2 + 2*(1)= 0.8
10*(-1.2) + 5*(1) = - 7

-1.2 + 2 = 0.8
- 12 + 5 = -7

0.8 = 0.8
-7 = -7

0